"Somos Asiáticos": Asian Americans, Latinos, and Hispanics of Asian ancestry. Issue 4 (December 2016) - Kang, Nancy; Torres-Saillant, Silvio
Abstract This essay seeks to challenge persistent readings of US race relations as being a contest between black and white. It reasserts the vitality and undeniable importance of Asian Americans and Latino/as (themselves harboring considerable Native American ancestry in their heritage) as the two fastest-growing minority populations in the country. Asian-Hispanic connections run the gamut from historical, economic, political, and cultural ties to collaborations in the arts and intermarriage. These intergroup relations have neither been wholly cooperative nor wholly adversarial given the immense variety of identities involved. This discussion aims to introduce a number of points of shared impact and concern, projecting a future of greater and more complex interactions.